The Effect of Intermittent Aircraft Noise Exposure to Occupational Stress on The Employee of Adi Sumarmo Airport in Boyolali - Dorothy Eugene Nindya Wiharjanto; R. Aj. Sri Wulandari; Sigit Setyawan (Nexus Kedokteran Komunitas, 2016)
Background: Noise is one of the most annoying environment hazard in the world, which is derived from various sources suchas aircraft. Aircraft noise is considered as the most annoying source, especially because of its intermittent. Noise can cause psychological disorders such as occupational stress. This research aims to determine the effect of aircraft noise to occupational stress on the employee of Adi Sumarmo Airport in Boyolali. Methods: This was an observational analytic research with cross-sectional design. The data were collected by using simple random sampling. Aircraft noise was measured with Sound Level Meter. The sample was 100 employees of Adi Sumarmo Airport which divided into the apron group and non apron group as control.Each respondent was given the standard questionnaire consist of identity form and informed consent, Lie-scale Minnesota Multiphasic Personality Inventory (LMMPI) questionnaire to determine the honesty of respondent, and International Stress Management Association (ISMA) questionnaire to measure occupational stress. All of the questionnaires were self reported. Statistical analysis was conducted with Chi Square test. Results: The noise in apron was 81.3 WECPNL and categorized as third level high noise area (WECPNL > 80). Check in area that represented the control had noise level of 61.14 WECPNL and not categorized as noise area. Respondents who met the acquirement were 86, consist of 43 in apron and 43 in non apron. In apron, 20 respondents (46.50%) had occupational stressand there were 8 respondents (18.60%) who had occupational stress in non apron. The result of Chi Square test for the effect of aircraft noise exposure to occupational stress showed p = 0.006. Conclusions:There was a significant effect of aircraft noise exposure to occupational stress on the employee of Boyolali Adi Sumarmo Airport. Keywords: aircraft noise, occupational stress